Entertainment computing -- ICEC 2016 : 15th IFIP TC 14 International Conference, Vienna, Austria, September 28-30, 2016, Proceedings /: 15th IFIP TC 14 International Conference, Vienna, Austria, September 28-30, 2016, Proceedings. (2016) - Unknown
No abstract available